2014
DOI: 10.1007/s12639-014-0530-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Toxoplasma gondii in Chicken samples from delta of Egypt using ELISA, histopathology and immunohistochemistry

Abstract: Estimates of the zoonotic diseases are helpful for monitoring and improving public health. Laboratory-based surveillance provides crucial information for assessing zoonotic disease trends and developments. Toxoplasmosis is considered as a zoonotic disease and has both medical and veterinary importance since it leads to abortion in humans and several animal species. In view of the worldwide importance of T. gondii, this study aimed to estimate the prevalence of T. gondii in chickens from the Delta of Egypt. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In Brazil, 70% of people have been exposed to T. gondii at some point in their lives (VERGARA et al, 1985). Indeed, serological studies conducted in different regions of the country have reported prevalence rates ranging from 11.18% to 78.7% (JAMRA & GUIMARÃES, 1981;FERRARONI & LACAZ, 1982;ABRAHAMS-SANDI & VARGAS-BRENES, 2005;HOLSBACK et al, 2012;ZHAO et al, 2012;IBRAHIM et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, 70% of people have been exposed to T. gondii at some point in their lives (VERGARA et al, 1985). Indeed, serological studies conducted in different regions of the country have reported prevalence rates ranging from 11.18% to 78.7% (JAMRA & GUIMARÃES, 1981;FERRARONI & LACAZ, 1982;ABRAHAMS-SANDI & VARGAS-BRENES, 2005;HOLSBACK et al, 2012;ZHAO et al, 2012;IBRAHIM et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Level of infection in chicken may be under detectable levels, and low parasitemia makes diagnosis in this model by microscopy difficult, needing ELISA or more sensible methods [38]. In some studies, already has been demonstrated that dose of parasites influence on studies, finding parasites in liver and heart, but none was found in brain cells.…”
Section: Bird Modelmentioning
confidence: 99%
“…Many species of birds can act as a reservoir for T. gondii, apparently with or without symptoms [39]. But some studies relating to gender prove that female chicken present more seroprevalence than male, probably associated to behavior manner [38].…”
Section: Bird Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Backyard production methods imply low biosafety measures and a high risk of infectious diseases (CONAN et al, 2012;IBRAHIM et al, 2016). Chickens reared in backyards, for instance, harbour a wide variety of geo-parasites, becoming highly infected during feeding (BEN SLIMANE, 2016;FERDUSHY et al, 2016;JAVAREGOWDA et al, 2016).…”
Section: Introductionmentioning
confidence: 99%